Daya Vermisidal Ekstrak Lima Jenis Etnofarmakologi terhadap Cacing Haemonchus contortus Secara In-vitro - I Gusti Komang Oka Wirawan; Kurniasih Kurniasih; Joko Prastowo; Wisnu Nurcahyo (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
Research aimed to identify the most effective concentration of five extract types (EKBMCP, EKPAS, EDMSP, EBJCP, dan EDMCO) as vermicidal anthelmintic against H. contortus in-vitro. Research was consisted of seven groups, among them five groups were considered as treatment groups that named based on the extract type (EKBMCP, EKPAS, EDMSP, EBJCP, dan EDMCO). Each treatment group was consisted five subgroups of etnopharmacological concentration : 0,5%, 1,5%, 2,5%, 3,5% dari 0,2 g/mL. Other two group were regarded as a negative control by distilled water treatment, and a positive control by pyrantel pamoat 5%. Every single treatment group was quadruplet and exposure each concentration were performed in quadruplet with variation in exposure times i.e. : 1, 3, 5, and 7 hours. The research focused on several variables that were the percentage of live and dead H. contortus in the treatment groups, extract concentration, and treatment period by using selected etnopharmacological extract. The effective vermicidal anthelmentic concentration of each treatment was analyzed descriptively. The results showed that five etnopharmacological extract types that were EKBMCP, EKPAS, EDMSP, EBJCP, dan EDMCO had a potency as vermicidal anthelmentic. Among those treatment, EKPAS and EBJCP had the lowest concentration (2,5%) to produce optimum vermicidal effect (100%) with period five hours exposure. Other treatment groups with EKBMCP and EDMSP needed 3,5% concentration with exposure period seven hours to produce optimum vermicidal effect, respectively. Another treatment group with EDMCO needed 3,5% concentration with exposure time seven hours to produce optimum vermicidal effect.